Effects of Various Recovery Strategies on Repeated Bouts of Simulated Intermittent Activity. Issue 7 (July 2019) - Crowther, Fiona A.; Sealey, Rebecca M.; Crowe, Melissa J.; Edwards, Andrew M.; Halson, Shona L.
Abstract : Abstract: Crowther, FA, Sealey, RM, Crowe, MJ, Edwards, AM, and Halson, SL. Effects of various recovery strategies on repeated bouts of simulated intermittent activity. J Strength Cond Res 33(7): 1781–1794, 2019—A large variety of recovery strategies are used between and after bouts of exercise to maximize performance and perceptual recovery, with limited conclusive evidence regarding the effectiveness of these strategies. The aim of this study was to compare 5 postexercise recovery strategies (cold water immersion, contrast water therapy, active recovery, a combined cold water immersion and active recovery, and a control condition) to determine which is most effective for the recovery of performance, perceptual, and flexibility measures during and after repeated bouts of simulated small-sided team sport demands. Fourteen recreationally active males (mean ± SD ; age: 26 ± 6 years; height: 180 ± 5 cm; mass: 81 ± 9 kg) undertook repeated bouts of exercise, simulating a rugby sevens tournament day followed by the above listed recovery strategies (randomized, 1 per week). Perceptual, performance, and flexibility variables were measured immediately before, 5 minutes after all 3 exercise bouts, and at 75 minutes after the first 2 exercise bouts. Contrast water therapy was found to be superior to active at 75 minutes after bout 2 and 5 minutes after bout 3 for repeated-sprint ability and relative average power. The combined recovery strategy was superior to active for repeated-sprint ability at 5 minutes after bout 3; relative best power at 5 minutes after bout 2; total quality recovery before bout 2, 75 minutes after bout 2, and before bout 3; was superior to active for muscle soreness from 75 minutes after bout 1 and for the remainder of the day; and was superior to the control at 75 minutes after bout 1, 75 minutes after bout 2, and before bout 3. The active recovery was detrimental to total sprint time and relative average power at 75 minutes after bout 2 and 5 minutes after bout 3 in comparison with contrast water therapy and the control (not relative average power). Relative average power was decreased after active at 5 minutes after bout 2 in comparison with the combined recovery strategy and the control. Relative average power after cold water immersion was decreased at 75 minutes after bout 2 in comparison with the control and contrast water therapy. Total quality recovery was significantly reduced after active in comparison with the combined recovery strategy before bout 2, 75 minutes after bout 2, and before bout 3. Muscle soreness was also significantly increased after active recovery at 75 minutes after bout 1 and for the remainder of the day in comparison with the combined recovery strategy and was increased at 5 minutes after bout 3 in comparison with the control. Active recovery is not recommended because of the detrimental performance and perceptual results noted. As no recovery strategies were significantly better than the control condition for performance recovery and the combined recovery strategy is the only superior recovery strategy in comparison with the control for perceptual recovery (muscle soreness only), it is difficult to recommend a recovery strategy that should be used for both performance and perceptual recovery. Thus, based on the methodology and findings of this study unless already in use by athletes, no water immersion recovery strategies are recommended in preference to a control because of the resource-intensive (time and equipment) nature of water immersion recovery strategies.